Unraveling the Secrets of Strategic Business Planning: A Pathway to Sustainable Growth and Competitive Advantage - Khuan, Hendri; Bambang, Bambang; Marlina, Milla; Aisyah Solehati (Eastasouth Institute, 2023)
This study aims to uncover the secrets of strategic business planning of startups in West Java, Indonesia, and its relationship with sustainable growth and competitive advantage. Through quantitative analysis of survey data from various startups, this study investigates the relationship between strategic planning practices, resource allocation, sustainable growth, and competitive advantage. The findings show that strategic planning practices and resource allocation are significantly correlated with sustainable growth and competitive advantage. These insights contribute to a deeper understanding of the dynamics of startups in the entrepreneurial ecosystem in West Java, providing valuable guidance for startups, policymakers, investors, and academics.